Modification of splenic stiffness on acoustic radiation force impulse parallels the variation of portal pressure induced by transjugular intrahepatic portosystemic shunt. Issue 3 (22nd February 2018) - De Santis, Adriano; Nardelli, Silvia; Bassanelli, Chiara; Lupo, Marinella; Iegri, Claudia; Di Ciesco, Carmela Anna; Forlino, Mariana; Farcomeni, Alessio; Riggio, Oliviero
Abstract: Background and Aim: Spleen and liver stiffness (LS) measured by acoustic radiation force impulse (ARFI) imaging has been shown to be useful in identifying patients with portal hypertension. The study aims to establish if the modification of portal pressure induced by a transjugular intrahepatic portosystemic shunt (TIPS) parallels the modification of spleen or LS measured by ARFI in order to understand if ARFI may be used to monitor the modification of portal pressure in patients with cirrhosis. Methods: Thirty‐eight patients with severe portal hypertension underwent LS and spleen stiffness (SS) before TIPS and 1 week after TIPS. Portal atrial gradient (PAG) was measured before and after the shunt opening. Results: Portal atrial gradient decreased significantly from 19.5 to 6 mmHg ( P  < 0.001). SS decreased significantly after TIPS (pre‐TIPS 3.7 m/s vs post‐TIPS 3. 1 m/s; P  < 0.001), and LS was also significantly modified by TIPS (pre‐TIPS 2.8 m/s vs post‐TIPS 2.4 m/s; P  = 0.003). PAG and SS values measured before and after TIPS were significantly correlated ( r  = 0.56; P  < 0.001); on the other hand, PAG and LS were not ( r  = 0.19; P  = 0.27). Two patients developed a persistent hepatic encephalopathy refractory to medical treatment and were submitted to the reduction of the stent diameter. The modification of SS was parallel to the modification of PAG. Conclusion: Spleen stiffness is superior to LS in detecting the modification of portal pressure induced by TIPS. This makes SS a potential non‐invasive method to monitor the modification of portal hypertension. Further investigations are needed to establish applicability and clinical utility of this promising tool in the treatment of portal hypertension.